Kinerja Individu Sebagai Pengukuran Kesuksesan Adopsi SIA dengan Model UTAUT dan Delone & Mc Lean - Pratama, Gede Surya; Ariyanto, Dodik; Aryista Dewi, Ayu (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
The research objective was to determine the effect of performance expectations, effort expectations, social influence and facilitation conditions as well as system quality and information quality on perceptions of individual performance in the Rural Bank accounting information system in Denpasar. The research population is individuals who use accounting information systems in carrying out their work. The research sample was taken using a purposive sampling technique, where the sampling process was based on certain criteria. So that the number of samples used in this study were 13 BPR  with a total of 100 BPR employees. Data collection using questionnaires and data analysis techniques used are multiple linear regression analysis. The results of the analysis in the study showed that: performance expectations (performance expectations), business expectations (business expectations), social factors (social influences), facilitation conditions (facilitation conditions), system quality and information quality had a positive and significant effect on individual performance. Keywords: UTAUT, De Lone and Mc Lean, individual performance.